Influence of Social Media Marketing on Purchase Intention of Gen Z - K. S. Deepika; Ajay Massand (The Scientific Temper, 2024)
Brand marketing activities on social media (SM) are becoming more innovative and attractive. With the growth of the internet and generation Z being the most likely users of internet technology(www.statista.com) and the potential market for products and services online, the study considers this group for analysis. The study aims to determine the factors impacting the purchase intention of Gen Z based on the social media marketing activities (SMMA) of the brand. The critical points analyzed are how Gen Z perceives brands marketed on SM and what characteristics they consider before their purchase. A sample size of 250 Gen Z customers is considered for the analysis. The research uses a purposive sampling technique amongst Gen Z as they are primarily into social media usage. The outcome of the research indicates to the marketers the most important aspects of social media marketing (SMM) that they have to focus on. Factor Analysis and Multiple Regression on the two factors obtained-customer engagement and trendiness has been employed. This research helps the brands design their SMMA focusing on the most vibrant factors that attract most of the specified target segment. It is of practical importance as Gen Z is the fresh entrant to the customer base of all brands. Gen Z’s changing behavior of adapting to new and trending social media platforms and leveraging of maximum time on social media along with easy access to the same makes it much more important for the marketers to focus on this research results.